Binary Janus Porous Coordination Polymer Coatings for Sensor Devices with Tunable Analyte Affinity1. Issue 1 (4th November 2012) - Meilikhov, Mikhail; Furukawa, Shuhei; Hirai, Kenji; Fischer, Roland A.; Kitagawa, Susumu
<x xml:space="preserve">Abstract</x> Janus MOF: Thin films consisting of non‐centrosymmetric heterostructured metal–organic frameworks (MOFs) were fabricated directly on quartz‐crystal microbalance (QCM) sensor devices. Depending on the spatial configuration of two frameworks, the thin MOF films could tune the affinity for analytes, thus giving high selectivity to the QCM sensors.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>